2014 IEEE International Symposium on Circuits and Systems (ISCAS) 2014
DOI: 10.1109/iscas.2014.6865665
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of magnetic flux profile in the presence of metamaterials for wireless power transfer

Abstract: We discuss the change in the magnetic flux profile by introducing a negative refractive index material (metamaterial) in between the source and receiver. The environment parameters, ε and μ , has a significant effect on the propagation of electromagnetic wave. The behavior of Transverse Magnetic (TM) wave when the medium in the path of propagation is changed to negative permittivity and permeability is simulated and discussed. The effect of size, shape and anisotrophy of the metamaterials, for near-field regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…By considering the thickness of the structure as 24 mm, the maximum refractive index "n 0 " and minimum refractive index "n(x)" values are found to be 1.82 and 1.276, respectively. For the above-mentioned specifications, it is found that the three-dimensional array is formed by 45 × 35 × 8 unit cells each of size 3 mm 3 . The three-dimensional CSR array is shown in Figure 5.…”
Section: Gradient Refractive Index Structurementioning
confidence: 99%
See 1 more Smart Citation
“…By considering the thickness of the structure as 24 mm, the maximum refractive index "n 0 " and minimum refractive index "n(x)" values are found to be 1.82 and 1.276, respectively. For the above-mentioned specifications, it is found that the three-dimensional array is formed by 45 × 35 × 8 unit cells each of size 3 mm 3 . The three-dimensional CSR array is shown in Figure 5.…”
Section: Gradient Refractive Index Structurementioning
confidence: 99%
“…In the near-field domain, inductive loops are used for energy transfer [1]. By the introduction of metamaterial in between the loops, the distance of energy transfer can be increased [2][3][4]. Most of the work in the far field is carried out in the microwave region [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%